The complete mitochondrial genome of the Rana sangzhiensis Shen and its phylogenetic analyses - Gang Xiong; Hui Jiang; Xiao-Qing Wang; Li Kang; Li Liu; Xian-Wen Zhou; Pei Wang; Tao Yang (Mitochondrial DNA. Part B. Resources, 2021)
The mitochondrial genome of one Rana pseudo-rana species Rana sangzhiensis Shen was sequenced and annotated. The mitogenome is 19,207 bp in length, containing 37 typical genes. The A + T content of the whole mitogenome is 56.6%. All of the protein-condoning genes (PCGs) started with ATG and stopped with TGA. The tRNA-Pro, tRNA-Gln, tRNA-Ala, tRNA-Asn, tRNA-Cys, tRNA-Tyr, tRNA-Ser, tRNA-Glu, andND5 are located in the circular mitochondrial L chain. The phylogeny tree is monophyletic among 14 related Rana species. The R. sangzhiensis Shen cluster was more closely related to R. amurensis Boulenger and R. kunyuensis Lu, Y.-Y., and P.-P. Li. This mitochondrial genome can be used for further analyses of Ranidae mitochondrial comparative genomics to improve the understanding of diverse Ranidae species.